The 7 habits of highly effective people : powerful lessons in personal change - Covey, Stephen R. (New York : Simon & Schuster, 2013)
A leading management consultant outlines seven organizational rules for improving effectiveness and increasing productivity at work and at home.
Foreword to the 25th anniversary edition / by Jim Collins -- A Cove family tribute to a highly effective father -- Foreword to the 2004 edition / By Stephen R. Covey -- Paradigms and principles. Inside-out -- The 7 habits : an overview -- Private victory. Habit 1 : be proactive : principles of personal vision -- Habit 2 : begin with the end in mind : principles of personal leadership -- Habit 3 : put first things first : principles of personal management -- Public victory : paradigms of interdependence. Habit 4 : think win/win : principles of interpersonal leadership -- Habit 5 : seek first to understand, then to be understood : principles of empathic communication -- Habit 6 : synergize : principles of creative cooperation -- Renewal. Habit 7 : sharpen the saw : priniciples of balanced self-renewal -- Inside-out again -- Afterword -- Appendix A. Possible perceptions flowing out of various centers -- Appendix B. A quadrant II day at the office -- A final interview with Stephen R. Covey -- Problem/opportunity index.
Previously published: New York : Free Press, c2004.
This edition has a new foreword by Jim Collins, a family tribute by Covey's children, and "A final interview with Stephen R. Covey."
Includes indexes.
Keywords: Success -- Psychological aspects; Character; Character; Conduct of life; Success -- Psychological aspects; Achievement; Character